Assuan, Ägypten. Felsinschriften und Felsbilder der Region von Assuan. Die Arbeiten der Jahre 2017 und 2018 - Seidlmayer, Stephan J. (e-Forschungsberichte des DAI, 2018)
Rock Art and Rock Inscriptions constitute a significant component of the archaeological record in the area of the First Cataract of the Nile. Inscribed onto the natural landscape itself these epigraphic markings offer a unique chance to reconstruct the social and cultural uses of space within a complex historical setting. During the last few years the focus of the project’s work temporarily shifted from recording inscriptions in the field to working out final publications, both digital and in print. In this project phase important progress in the contextual analysis of the data could be achieved.